Exploration of experiences of patients with the adverse-drug effects of multidrug-resistant tuberculosis treatment in a primary health care facility in the Western Cape - Tinzi, Siphokuhle (University of the Western Cape, 2017)
Magister Curationis - MCur === Multidrug resistant TB (MDR-TB) is a form of TB caused by bacteria (germs) that are resistant to the usual drugs that are used to treat "normal" TB. The duration of treatment for MDR-TB is a maximum of 22 months. People with MDR-TB are treated in specialized tertiary hospitals and in out-patient clinics in the PHC facilities. The treatment includes a six months injectable phase with a wide range of TB drugs. The adverse effects of MDR-TB drugs are among the worst side effects ever reported by patients. The aim of the current study was to explore the experiences of adverse effects of MDR-TB treatment amongst patients in a primary health care facility in the Western Cape. An explorative qualitative study design was used to explore the experiences of patient with the adverse effects of MDR-TB treatment in a primary health care facility in the Western Cape. In depth interviews were conducted with 12 MDR-TB patients. Data analysis was done by using the Tesch's method of content analysis. The study revealed that participating MDR-TB patients experienced various emotional, financial, physical and social challenges. Participants explained that the experience of being on MDR-TB treatment is emotionally draining; the pain and discomfort of the adverse effect of treatment makes a person to feel anxious and depressed. Financially they depended on social grants because they had to stop working after starting treatment. They could not function well physically because of the toxic nature of the adverse effects of treatment; which resulted in fatigue, dizziness and burning sensation on the feet and hands. They were faced with a lot of stigma from the community and even family members because of their illness. The study also revealed that in spite of the challenges and obstacles the participants were all motivated to complete their treatment and get cured. It is recommended that more support structures be made available for patients who are being treated for MDRT-TB such as; psychotherapy, social support and counselling on health education. Provision needs to be made for patients who are receiving daily injection; for it to be given in their homes. Health care providers treating MDR-TB patients need to do home visits together with MDR-TB adherence counsellors, to monitor the physical wellbeing of patients at home. This will also provide patients with the platform to discuss their health concerns in a more accommodative and relaxed environment. New drug regimen with fewer tablets and less treatment duration is needed for MDR-TB.